METODE RAá¹¢DU QIBLAH DENGAN BEDA AZIMUT DALAM PENENTUAN ARAH KIBLAT (IAIN Tulungagung, 2019)
Raá¹£du Qiblah is a method of determining the direction of qibla which is known to be economical, practical and accurate. In practice, Raá¹£du Qiblah is restricted due to the presence of the sunray and the limited time. As the result, the Raá¹£du Qiblah formula with azimuthal angle is developed as a solution which can be utilized four times or more in a day. This research employs a quantitative approach with mathematical analysis to describe the accuracy of the method. The findings of this study are that the calculation of the Raá¹£du Qiblah with different azimuth approaches the solar azimuth calculation results at any time. The results of the practice also approach the local Raá¹£du Qiblah which means that the accuracy of this method is almost the same as the original method and can be used as an alternative for determining the accurate direction of qibla.Keywords: Raá¹£du Qiblah, Difference of Azimuth, Astronomy